2012
DOI: 10.1016/j.jnucmat.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Heavy ion irradiation induced dislocation loops in AREVA’s M5® alloy

Abstract: Heavy ion irradiation induced dislocation loops in AREVA's M5 alloy Cover letter for the second revised submission of the article to the Journal of Nuclear MaterialsPressurized water reactor (PWR) Zr-based alloy structural materials show creep and growth under neutron irradiation as a consequence of the irradiation induced microstructural changes in the alloy. A better scientific understanding of these microstructural processes can improve simulation programs for structural component deformation and simplify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…1. The damage, D, in displacements per atom (dpa), and hence the damage rate at 12 lm depth was calculated to be $7.5 Â 10 À6 dpa h À1 using the following equation [25]:…”
Section: Experimental Methodsmentioning
confidence: 99%
“…1. The damage, D, in displacements per atom (dpa), and hence the damage rate at 12 lm depth was calculated to be $7.5 Â 10 À6 dpa h À1 using the following equation [25]:…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In M5 alloy irradiated by 1 MeV Kr ions the size and density of hai-type dislocation loops increase with dose at 573 K from 0.1 to 17 dpa. In addition, hci-type dislocation loops are not present until at the dose of 6.8 dpa [5]. It was discussed above that the study by Yamada and Kameyama [6] showed that high temperature of 673 K enhances the formation of hci-type dislocation loops.…”
Section: Hardness and Modulus Measurementsmentioning
confidence: 95%
“…It is found that the size and density of dislocation loops and the threshold dose of hci-type dislocation loops depend strongly on irradiation temperature. Hengstler-Eger et al [5] studied the hai-and hci-type dislocation loops evolution in Kr 2+ irradiated M5. During the annealing process, the size of hci-type dislocation loops increases while the density decreases.…”
Section: Introductionmentioning
confidence: 99%
“…In this analysis, we assume that the hardening of irradiated samples as compared to that of the unirradiated samples is solely attributed to the irradiation-induced precipitation of Nb nanoclusters. However, in reality, defect clusters such as dislocation loops are also introduced by high-energy particle irradiation [44,45]; furthermore, Fe nanoclusters are produced in high-damage samples. Since those factors are not considered in the present analysis, the a determined for Nb nanoclusters is overestimated.…”
Section: Obstacle Strength Of Irradiation-induced Nb Nanoclustersmentioning
confidence: 99%